2016
DOI: 10.1007/s12565-015-0324-8
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation alterations in experimentally induced gingivitis in dogs

Abstract: The present study aimed to morphologically examine the gingival microvascular network using a microvascular resin cast (MRC) technique, and to investigate how inflammatory disease functionally affects gingival microcirculation using laser Doppler flowmetry (LDF). We used four beagle dogs with healthy periodontal tissue as experimental animals. To cause periodontal inflammation, dental floss was placed around the cervical neck portions of the right premolars. The unmanipulated left premolars served as controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Other studies on dogs have shown that predictable morphologic changes occur in the blood vessels at the gingival margin with the onset of inflammation. These vascular changes precede recognizable histopathological alterations, starting as early as 2 days after the induction of gingivitis [36,37,83].…”
Section: Microcirculation Of the Gingivamentioning
confidence: 96%
“…Other studies on dogs have shown that predictable morphologic changes occur in the blood vessels at the gingival margin with the onset of inflammation. These vascular changes precede recognizable histopathological alterations, starting as early as 2 days after the induction of gingivitis [36,37,83].…”
Section: Microcirculation Of the Gingivamentioning
confidence: 96%
“…Our previous study recently proved that functional analyses using a single index may not be accurate and should be accompanied by appropriate morphological analyses. 22 In this study, we demonstrated, by using morphological and physiological approach, that ultrasonic wave instruments cause minimal damage to gingival microcirculation, compared with a dental turbine.…”
Section: Discussionmentioning
confidence: 73%
“…[16][17][18][19][20][21] Recently, the LDF has been applied to determine blood flow alterations with high reproducibility in the maxillofacial region, including the gingival mucosa, and gingival vascular function. [22][23][24][25] The aim of this study was to determine whether ultrasonic preparation led to alterations in blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…The rats from each group were bled under pentobarbital sodium (45 mg/kg, intraperitoneally) anesthesia by perfusing 0.2% heparin in saline into the ascending aorta. The tissue was fixed and perfused in 10% neutral buffered formalin solution to maintain the vascular lumens [35]. After perfusing ink into the blood vessels, the maxilla was excised, hard tissue was decalcified using hydrochloric acid, and the specimens were embedded in paraffin to obtain 50-μm-thick sections.…”
Section: Morphological Analysismentioning
confidence: 99%